Development of process protocol to enhance the phospholipid content of ghee residue - Krishnegowda, Rajesh; Sharma, Monika; Menon Ravindra, Rekha; Jose, Naveen (Indian Journal of Dairy Science, 2024)
Many by-products of the dairy industry contain nutritive and commercial value, which with appropriate technological interventions can be exploited for improving the profitability of the industry. Ghee residue is one such by-product reported to contain considerable amount of polar lipids dominated by phospholipids (PLs). An attempt was made to develop a stepwise protocol to enhance the PL content in ghee residue, to facilitate its efficient and economical extraction from the residue matrix. Firstly, mechanical expression of residual lipids in the ghee residue matrix was evaluated using hydraulic press at different pressures. Pressing at 5 kg/cm2 for 5 min. resulted in the maximum separation of lipids, resulting in a 13% exudation of lipids out of ghee residue matrix. Further increase in pressure did not significantly influence lipids expression from ghee residue matrix. Two solvents, one each of polar and a non-polar nature, were then studied to separate neutral lipids from total lipids present in the pressed residue. N-hexane (the non-polar solvent) successfully demonstrated the separation, and the PL content in n-hexane treated sample was 26.22, 24.68 and 21.29%, when treated at solvent to solid ratio of 1:4, 1:3 and 1:2, respectively for contact time of 30 min. Extraction of neutral lipids from the ghee residue matrix using boiling water showed a 27.03% retention of its lipid content with a simultaneous removal of 16.93% lipids, at a solid to water ratio of 1:4 for contact time of 60 min. This led to appreciable enrichment of phospholipids in the reside matrix with concentration of 8.26% on ghee residue basis and 30.56% on fat basis, indicating significant increase in total phospholipids after separation of neutral lipids. Comminution of boiled water treated ghee residue showed further increase of phospholipids, with a PL content of 9.56% against 9.32% for ghee residue comminuted to 0.25 mm and 0.30 mm, respectively. Thus, it can be concluded that application of the physical and chemical interventions significantly improved the phospholipid content of ghee residue.